Answer:
Its E c;
Step-by-step explanation:
Answer:
Distributive property says that:
(A + B)*C = A*C + B*C
Now let's try to use it in our expression:
3 + 5*c*(2 + 6*c)
Here we can take the two terms inside the parentheses as A and B, and the term that multiplies them as C, then distributing we get:
3 + (5*c)*2 + (5*c)*(6*c)
Now remember that the multiplications are associative and commutative, then we can write this as:
3 + (2*5)*c + (5*6)*(c*c)
3 + 10*c + 30*c^2
And we can't simplify it anymore.
Answer:
y = -3/2x + 3
Step-by-step explanation:
First, know that slope-intercept form is y = mx + b. Since our y-intercept is 3, we can plug that in for B, and since the slope goes down 3 and over to the right 2, it is -3/2. So, when everything's plugged in, we get y = -3/2x + 3.
I hope this helped! Please leave Brainliest if it did.
20% chance for the letter box and 25% chance for Number box.
<span>The ratio of 2 similar areas is the square of the ratio of their RADIUS or (sides)
R²=(2/3)² = 4/9 This should be the answer
Whereas R³ = (2/3)³ = 8/27 is the ratio of their volume & not area
</span>